Diabetes mellitus due to agenesis of the dorsal pancreas in a patient with heterotaxy syndrome - Jo Eun Jung; Jin Ho Hur; Mo Kyung Jung; Ahreum Kwon; Hyun Wook Chae; Duk Hee Kim; Ho-Seong Kim (Korean Society of Pediatric Endocrinology, 2017)
Heterotaxy syndrome (HS) is a congenital disorder resulting from an abnormal arrangement of visceral organs across the normal left-right axis in the embryonic period. HS is usually associated with multiple anomalies, including defects of the major cardiovascular system and the extracardiovascular system such as intestinal malrotation, abnormal lung lobulation, bronchus anomalies, and pancreatic dysplasia. Although pancreatic dysplasia is occasionally accompanied with HS, the occurrence of diabetes mellitus (DM) due to pancreatic dysplasia in HS is rarely reported. We here report a case involving 13-year-old girl with DM caused by agenesis of the dorsal pancreas and HS diagnosed on the basis of the presence of a double-outlet right ventricle with bilateral pulmonary stenosis and intestinal malrotation with duodenal cyst. Timely diagnosis and treatment with insulin improved glycemic control.